Public Transportation as a Strategic Tool for Sustainable Development - Santos, Rodrigo Maia; Ferreira, Denise Helena Lombardo; Sugahara, Cibele Roberta; Silva Filho, Cândido Ferreira da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Globally, the significant growth in the number of motorized road vehicles has been evident in recent decades. This article focuses on analyzing public transportation as a public policy within the context of urban mobility for sustainable development. The research methodology employed is applied, bibliographical, and qualitative in nature. The results highlight the need to establish definitions and guidelines for the urban mobility to take place by encouraging and investing in the search for public transportation means as environmentally and socially viable alternatives as a way to contribute to mitigating global warming and achieving Goal 11.2 of the Sustainable Development Goal number 11.